Effects of endogenous small molecular compounds on the rheological properties, texture and microstructure of soymilk coagulum: Removal of phytate using ultrafiltration. (15th November 2016) - Wang, Ruican; Guo, Shuntang
Highlights: Relationship between coagulation rate and corresponding gel structure was well established. Removal of small molecules resulted in coarsened gel matrix. Coagulation could be controlled by adjusting the amount of some small molecules. Small molecules, like phytate, were essential to the formation of fine gel network. Abstract: This study aims to clarify the roles played by endogenous small molecular components in soymilk coagulation process and the properties of gels. Soymilk samples with decreasing levels of small molecules were prepared by ultrafiltration, to reduce the amount of phytate and salts. CaSO4 -induced coagulation process was analyzed using rheological methods. Results showed that removal of free small molecules decreased the activation energy of protein coagulation, resulting in accelerated reaction and increased gel strength. However, too fast a reaction led to the drop in storage modulus (G′). Microscopic observation suggested that accelerated coagulation generated a coarse and non-uniform gel network with large pores. This network could not hold much water, leading to serious syneresis. Endogenous small molecules in soymilk were vital in the fine gel structure. Coagulation rate could be controlled by adjusting the amount of small molecules to obtain tofu products with the optimal texture.